Do Young Inspire to be an Entrepreneur? A Case of Secondary Students Perception in Malaysia - Ahmad Zubir Ibrahim; Shazida Jan Mohd Khan; Abdul Rahim Anuar (International Review of Management and Marketing, 2017)
Youth plays an important role in the nation development. They were the future leader and development partners that drives towards the development of the nations. The ability to harness their potential as entrepreneur will helps to determine the nation strength and resilience in pursuing social, economic and political development. Therefore, providing proper environment and opportunities will be essential to inspire youth in becoming an entrepreneur. This paper will look into factors affecting youth intention (with target group of secondary school pupil in Malaysia) of becoming entrepreneur. The finding indicates that only 144 students from a sample of 1011 secondary students in Malaysia have interest to engage in entrepreneurship upon completion of schooling although various approaches have been made to increase youths participating in entrepreneurship. This study also suggested with recommendations to enhance and review existing curriculum entrepreneurship education for improve youth intention of becoming entrepreneur.